UDK 677.21.021 ANALYSIS OF COTTON FLOW BEHAVIOR IN DIFFERENT PNEUMATIC PIPES - Mukhametshina, Elmira (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Abstract. Objective. This article presents an analysis of the flow of cotton in different pneumatic pipes in the pneumatic transport system used in the delivery of cotton to the production workshops located in the cotton gin. Despite the fact that many scientific researches have been carried out to improve the components of the pneumatic transport system in the process of transporting cotton by pneumatic transport, researches on the pneumatic pipe and its hermeticity and the friction of the pipe with cotton have not been sufficiently studied in order to ensure the efficiency of the cotton raw material transportation in the air flow. In tube mills, seeded cotton hits the working surfaces and the resulting contact stresses are a major cause of seed and fiber damage. Three types of pneumatic elbows are proposed, namely ellipse, parabola and radial elbows. The analysis of cotton movement on three types of corner section is studied. Therefore, the main goal of the article is to study the analysis of cotton flow in pneumatic pipe.